Comparative analysis of the complete chloroplast genome sequences of three Amaranthus species. Issue 3 (24th January 2019) - Hong, Su-Young; Cheon, Kyeong-Sik; Yoo, Ki-Oug; Lee, Hyun-Oh; Mekapogu, Manjulatha; Cho, Kwang-Soo
Abstract: The complete chloroplast (cp) genome sequences of three Amaranthus species ( Amaranthus hypochondriacus, A. cruentus and A. caudatus ) were determined by next-generation sequencing. The cp genome sequences of A. hypochondriacus, A. cruentus and A. caudatus were 150, 523, 150, 757 and 150, 523 bp in length, respectively, each containing 84 genes with identical contents and orders. Expansion or contraction of the inverted repeat region was not observed among the three Amaranthus species. The coding regions were highly conserved with 99.3% homology in nucleotide and amino acid sequences. Five genes – matK, accD, ndhJ, ccsA and ndhF – showed relatively high non-synonymous/synonymous values ( K a / K s > 0.1). Sequence comparison identified two insertion/deletion (InDels) greater than 40 bp in length, and polymerase chain reaction markers that could amplify these InDel regions were applied to diverse Korean Genbank accessions, which could discriminate the three Amaranthus species. Phylogenetic analyses based on 62 protein-coding genes showed that the core Caryophyllales were monophyletic and Amaranthoideae formed a sister group with the Betoideae and Chenopodioideae clade. Comparing each homologous locus among the three Amaranthus species, identified eight regions with high Pi values (>0.03). Seven of these loci, except for rps19-trnH ( GUG ), were considered to be useful molecular markers for further phylogenetic studies.